Rules of thumb for maintenance and reliability engineers - Smith, Ricky (Elsevier/Butterworth-Heinemann, 2008)
Rules of Thumb for Maintenance and Reliability Engineers will give the engineer the have to have information. It will help instill knowledge on a daily basis, to do his or her job and to maintain and assure reliable equipment to help reduce costs. This book will be an easy reference for engineers and managers needing immediate solutions to everyday problems. Most civil, mechanical, and electrical engineers will face issues relating to maintenance and reliability, at some point in their jobs. This will become their go to book. It will be the only book on the market with this scope and usability. Not an oversized handbook or a theoretical treatise, but a handy collection of graphs, charts, calculations, tables, curves, and explanations, basic rules of thumb that any engineer working with equipment will need for basic maintenance and reliability of that equipment. access to quick information which will help them in day to day and long term engineering solutions in reliability and maintenance listing of short articles to help assist engineers in resolving problems they face written by two of the top experts in the country.
Keywords: Systems engineering -- Management.; Reliability.; elektronické knihy; electronic books